How Threat Assessment Could Become Self-Fulfilling Prophecy: Case of U.S.-China Relations - Arif, Muhamad (Global: Jurnal Politik Internasional, 2016)
This article tries to explain how misperception can trigger conflict between countries. The article would employ spiral model of conflict proposed by Robert Jervis as a theoretical framework to scrutinize contemporary US and Chinese contemporary competition. As a result, this paper shows how threat assessment could trigger a spiral of conflict through state’s tendency to overestimate threat level and its failure to perceive that defensive behavior can be interpreted as offensive by the belligerent. Based on this analysis, the probability of conflicts can be reduced as each country tries to comprehend motivations that drive other behavior, perceptions and reactions that might arise as a result of the strategic empathy.